Interdisciplinary Management of Palatogingival Groove in Maxillary Lateral Incisor - Bhattarai, Anjali; Pokharel, Regan; Pradhan, Ameena; Joshi, Neera (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Palatogingival groove is a developmental anomaly usually affecting maxillary anterior teeth. This is often accompanied by bone destruction adjacent to the teeth with no carious or traumatic history. This groove can harbor plaque and bacteria, resulting in periodontal destruction, endodontic lesions, or combined endodontic-periodontal lesions. Disease severity and prognosis depend on several factors, including location, range, depth, and type of the groove. Several materials have been used and recommended for cases of extensive periodontal destruction to remove and block the inflammatory source and recover the health of surrounding periodontal tissues, hence successfully managing the condition.